Glacial-related morphology and sedimentary setting of a high-latitude lacustrine basin: The Lago Chepelmut (Tierra del Fuego, Argentina). (October 2018) - Lozano, Jorge G.; Tassone, Alejandro; Bran, Donaldo M.; Lodolo, Emanuele; Menichetti, Marco; Cerredo, María E.; Esteban, Federico; Ormazabal, Juan P.; Ísola, José; Baradello, Luca; Vilas, Juan F.
Abstract: Lago Chepelmut is a relatively small lake in size, of ellipsoidal shape, located in the outer fold-and-thrust belt of the Fuegian Andes (southernmost South America). High-resolution single-channel seismic profiles, integrated with geological information in the surrounding area, have allowed to reconstruct for the first time a bathymetric map of the lake and the architecture, distribution and thickness of the sedimentary cover. Two main seismic units were identified in the seismic records: (i) a Lower Unit of glacial nature, likely associated to the Last Glacial Maximum (LGM), and irregularly distributed through the basin, and (ii) an Upper Unit of lacustrine origin which drapes the entire basin. Submerged moraine deposits within the lake were also found from seismic data, and correlated with moraine arcs widespread distributed in the surroundings of the basin. These morphologies represent the recessional deposits left by the Ewan glacier lobe, one of the easternmost fronts of the Tierra del Fuego glaciers during the LGM. The lacustrine sedimentary record shows that the lake level was not constant through the recent history of the lake. Moreover, data analysis has shown that there is also an important structural component that has conditioned the evolution of the basin, in addition to that linked to glacial activity. Highlights: We present a study of a seismic survey in Lago Chepelmut basin, located in Tierra del Fuego. Two seismic units are recognized within the basin, a glacial-related lower unit and a lacustrine upper unit. The basin is interpreted mainly as an ice-carved basin by the glacier lobes. We suggest that three major drops in the lake levels are evidenced in the stratigraphic record.